Cell-adhesion Molecules as Key Mechanisms of Tumor Invasion: The Case of Breast Cancer - Luís, Carla; Soares, Raquel; Fernandes, Rúben; Botelho, Mónica (Current Molecular Medicine, 2023)
Cancer is a major health problem worldwide and the second leading cause of death following cardiovascular diseases. Breast cancer is the leading cause of mortality and morbidity among women and one of the most common malignant neoplasms prompt to metastatic disease. In the present review, the mechanisms of the major cell adhesion molecules involved in tumor invasion are discussed, focusing on the case of breast cancer. A non-systematic updated revision of the literature was performed in order to assemble information regarding the expression of the adhesion cell molecules associated with metastasis.
Keywords: metastasis